Lithium manganese iron phosphate composite material, preparation method and related device

By using the preparation method of lithium manganese iron phosphate composite material in the positive electrode active material of the battery, the problem of low compaction density of the positive electrode active material is solved, the battery discharge specific capacity is improved, and the process flow is simplified.

CN119873777APending Publication Date: 2025-04-25CATL (JIANGSU) NEW ENERGY TECHNOLOGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311398292.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The compaction density of existing positive electrode active materials is low, resulting in a lower discharge specific capacity of the battery.

Method used

Using a preparation method of lithium manganese iron phosphate composite material, a manganese hydrogen phosphate precursor is formed by reacting phosphoric acid, an inorganic manganese source and a reducing agent under a reducing atmosphere, and mixing it with the M source and carbon source, then spray granulation to form a lithium manganese iron phosphate precursor, and finally calcined under an inert atmosphere to form a composite material including lithium manganese iron phosphate particles and a carbon cladding layer.

Benefits of technology

The compaction density of the positive electrode active material is improved, thereby increasing the discharge specific capacity of the battery, simplifying the preparation process, and reducing the generation of wastewater and impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873777A_ABST
    Figure CN119873777A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium manganese iron phosphate composite material, a preparation method and a related device. The preparation method comprises the steps that phosphoric acid, an inorganic manganese source and a reducing agent are added into a solvent, manganese ions in the inorganic manganese source are reduced into divalent manganese ions in the reducing atmosphere, so that the divalent manganese ions and phosphoric acid react to generate a manganese hydrogen phosphate precursor, and the valence state of the manganese ions in the inorganic manganese source is higher than that of the divalent manganese ions; mixing an M source, the manganese hydrogen phosphate precursor and a carbon source, grinding, and performing spray granulation to form a lithium iron manganese phosphate precursor, the M source including an iron source and a lithium source; and calcining the lithium manganese iron phosphate precursor in an inert atmosphere to generate the lithium manganese iron phosphate composite material, the lithium manganese iron phosphate composite material comprises lithium manganese iron phosphate particles and a carbon coating layer, and the carbon coating layer coats at least part of the outer surface of the lithium manganese iron phosphate particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a lithium manganese iron phosphate composite material, a preparation method, and related devices. Background Art

[0002] Battery cells are widely used because of their reliable working performance, no pollution, and no memory effect. For example, as environmental protection issues are increasingly valued and new energy vehicles become more popular, the demand for power battery cells will show explosive growth.

[0003] As the application range of batteries becomes wider and wider, the requirements for battery performance are becoming increasingly stringent. As an important component in the battery, the positive electrode active material has a significant impact on the battery performance. However, the compaction density of the positive electrode active material is low, resulting in a low discharge specific capacity of the battery. Summary of the invention

[0004] The present application provides a lithium manganese iron phosphate composite material and a preparation method and related devices, which can improve the compaction density of the positive electrode active material and improve the discharge specific capacity of the battery.

[0005] In a first aspect, the present application proposes a method for preparing a lithium manganese iron phosphate composite material, comprising:

[0006] Phosphoric acid, an inorganic manganese source and a reducing agent are added to a solvent, and manganese ions in the inorganic manganese source are reduced to divalent manganese ions under a reducing atmosphere, so that the divalent manganese ions react with phosphoric acid to generate a hydrogen manganese phosphate precursor, wherein the valence state of the manganese ions in the inorganic manganese source is higher than divalent;

[0007] The M source, the manganese hydrogen phosphate precursor and the carbon source are mixed, and after grinding, spray granulation is performed to form a manganese iron phosphate lithium precursor, wherein the M source includes an iron source and a lithium source;

[0008] The lithium iron manganese phosphate precursor is calcined in an inert atmosphere to generate a lithium iron manganese phosphate composite material, wherein the lithium iron manganese phosphate composite material includes lithium iron manganese phosphate particles and a carbon coating layer, and the carbon coating layer is coated on at least a portion of the outer surface of the lithium iron manganese phosphate particles.

[0009] According to the preparation method of the embodiment of the present application, an inorganic manganese source, a reducing agent and phosphoric acid react to form a hydrogen manganese phosphate precursor. This process basically does not require dehydration and drying, is not easy to generate wastewater, and is not easy to introduce impurity anions and metal ions; the hydrogen manganese phosphate precursor, an iron source, a phosphorus source, a lithium source and a carbon source are spray granulated to form a lithium iron manganese phosphate precursor with a relatively small particle size; the lithium iron manganese phosphate precursor is calcined to form a lithium iron manganese phosphate composite material, which includes lithium iron manganese phosphate particles and a carbon coating layer, the lithium iron manganese phosphate particles have a good crystal structure and can improve the compaction density of the lithium iron manganese phosphate particles, the carbon coating layer can improve the electronic conductivity of the lithium iron manganese phosphate composite material, and improve the overall conductivity of the lithium iron manganese phosphate composite material; when the lithium iron manganese phosphate composite material is used in a battery, the discharge specific capacity of the battery can be improved.

[0010] In some embodiments, the inorganic manganese source includes at least one of manganese dioxide and trimanganese tetraoxide.

[0011] In some embodiments, the reducing agent includes at least one of hydrogen peroxide and oxalic acid.

[0012] In some embodiments, the ratio of the molar amount of the inorganic manganese source to the molar amount of phosphoric acid is (0.3 to 2.0): 1, and can be (0.80 to 1.05): 1. When the ratio of the molar amount of the inorganic manganese source to the molar amount of phosphoric acid is within the above range, it is beneficial to the formation of the manganese hydrogen phosphate precursor.

[0013] In some embodiments, the ratio of the molar amount of the reducing agent to the molar amount of the inorganic manganese source is (1.0 to 1.5): 1; optionally (1.05 to 1.5): 1. When the ratio of the molar amount of the reducing agent to the molar amount of the inorganic manganese source is within the above range, the reducing agent can reduce the manganese ions in the inorganic manganese source to divalent manganese ions, which is beneficial to the subsequent formation of a manganese hydrogen phosphate precursor.

[0014] In some embodiments, the lithium source includes at least one of an inorganic lithium source and an organic lithium source; optionally, the inorganic lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate and lithium phosphate; optionally, the organic lithium source includes at least one of lithium acetate, lithium oxalate and lithium citrate.

[0015] In some embodiments, the iron source includes at least one of an inorganic iron source and an organic iron source; optionally, the inorganic iron source includes at least one of ferrous carbonate, ferric phosphate, and ferrous hydrogen phosphate; the organic iron source includes at least one of ferrous oxalate and ferrous acetate.

[0016] In some embodiments, the carbon source includes at least one of a hydroxyl-containing compound and a polyolefin compound; optionally, the hydroxyl-containing compound includes ethylene glycol, glucose, sucrose, polyethylene glycol PEG, polyvinyl alcohol P vA, at least one of citric acid and hydroxypropyl beta-cyclodextrin; the polyolefin compound includes polyvinyl pyrrolidone P v P, acrylic resin PAA, polyvinylidene fluoride P v At least one of DF, polystyrene and polypropylene.

[0017] In some embodiments, the ratio of the molar amount of the lithium source, the molar amount of the iron source, and the molar amount of the manganese hydrogen phosphate precursor is 1: (0.35 to 0.60): (0.20 to 0.85). When the molar amount ratio of the lithium source, the iron source, and the manganese hydrogen phosphate precursor is within the above range, the desired lithium iron manganese phosphate precursor system can be prepared, and the content of each element in the system is stable.

[0018] In some embodiments, the M source further includes a doping source, and the doping elements in the doping source include at least one element selected from titanium, vanadium, chromium, copper, magnesium, aluminum, zinc, cobalt, nickel, tin, niobium, tungsten, zirconium, tantalum, cerium, europium and fluorine.

[0019] In some embodiments, the step of mixing the M source, the manganese hydrogen phosphate precursor and the carbon source, grinding and then spray granulating to form the lithium manganese iron phosphate precursor comprises:

[0020] The M source and the manganese hydrogen phosphate precursor are mixed, and a carbon source is added to the mixture, and after grinding, spray granulation is performed to form a first lithium manganese iron phosphate precursor;

[0021] Mixing an M source and a manganese hydrogen phosphate precursor, adding a carbon source, and grinding and spray granulating to form a second lithium manganese iron phosphate precursor, wherein the volume average particle size of the first lithium manganese iron phosphate precursor is larger than the volume average particle size of the second lithium manganese iron phosphate precursor;

[0022] The first lithium iron manganese phosphate precursor and the second lithium iron manganese phosphate precursor are mixed to form a lithium iron manganese phosphate precursor.

[0023] Therefore, the embodiment of the present application prepares a first lithium iron manganese phosphate precursor and a second lithium iron manganese phosphate precursor of two different particle sizes, mixes the two powders in proportion and sinters them to grow into primary particles of different sizes, thereby improving the compaction density by grading the size of the particles.

[0024] In some embodiments, the volume average particle size D of the first lithium manganese iron phosphate precursor is v 50 is 14μm to 15μm.

[0025] In some embodiments, the volume average particle size D of the second lithium manganese iron phosphate precursor is v 50 is 13μm to 14μm.

[0026] In some embodiments, based on the total mass of the lithium iron manganese phosphate precursor, the ratio of the mass content of the first lithium iron manganese phosphate precursor to the mass content of the second lithium iron manganese phosphate precursor is (10:90) to (30:70).

[0027] In a second aspect, the present application proposes a lithium manganese phosphate composite material, comprising lithium manganese phosphate particles and a carbon coating layer coated on at least a portion of the surface of the lithium manganese phosphate particles, wherein the lithium manganese phosphate particles include a molecular formula of Li a Fe x Mn y M z PO4 compound, wherein 1.00≤a≤1.05, 0.1≤x≤0.5, 0.5≤y≤0.9, 0.95≤x+y≤0.98, 0.002≤z≤0.025, and the M element includes at least one element selected from titanium, vanadium, chromium, copper, magnesium, aluminum, zinc, cobalt, nickel, tin, niobium, tungsten, zirconium, tantalum, cerium, europium and fluorine.

[0028] In some embodiments, the mass content of the carbon coating layer relative to the total mass of the lithium manganese iron phosphate composite material is 1.3% to 1.6%. The carbon coating layer can provide good protection for the material and improve electronic conductivity, which is beneficial to further slow down the polarization of the material.

[0029] In some embodiments, the lithium manganese iron phosphate composite material satisfies at least one of the following conditions:

[0030] (1) The compaction density of the lithium manganese iron phosphate composite material under a force of 20,000 N is 2.10 g / cm 3 Up to 2.45g / cm 3 ;

[0031] (2) Volume average particle size D of lithium manganese iron phosphate composite material v 50: 0.8 μm to 1.2 μm;

[0032] (3) The lithium manganese iron phosphate composite material includes a first particle and a second particle, wherein the primary particle size of the first particle is larger than the primary particle size of the second particle; optionally, the primary particle size of the first particle is 0.45 μm to 0.6 μm; and / or the primary particle size of the second particle is 0.10 μm to 0.25 μm.

[0033] In some embodiments, based on the total mass of the lithium manganese iron phosphate composite material, the ratio of the mass percentage of the first particles to the mass percentage of the second particles is (10:90) to (30:70).

[0034] In the third aspect, the present application proposes a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes a lithium iron manganese phosphate composite material prepared by the preparation method of any embodiment of the first aspect of the present application, or a lithium iron manganese phosphate composite material of any embodiment of the second aspect of the present application.

[0035] In a fourth aspect, the present application proposes a battery, comprising a positive electrode plate as described in any embodiment of the third aspect of the present application.

[0036] In a fifth aspect, the present application proposes an electrical device, comprising a battery as described in any embodiment of the fourth aspect of the present application, wherein the battery is used to provide electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0038] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.

[0039] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.

[0040] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0041] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0042] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0043] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0044] Figure 7 It is a scanning electron microscope (SEM) schematic diagram of the lithium manganese iron phosphate composite material in Examples 1-51 of the present application.

[0045] The drawings are not necessarily drawn to scale.

[0046] The following are the descriptions of the reference numerals:

[0047] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0048] 5. Battery cell; 51. Housing; 52. Electrode assembly;

[0049] 53. Cover plate;

[0050] 6. Electrical equipment. DETAILED DESCRIPTION

[0051] Hereinafter, the embodiments of the lithium manganese iron phosphate composite material, positive electrode sheet, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0052] "Scope" disclosed in the present application is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following range can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0 to 5" means that all real numbers between "0 to 5" are listed in this document, and "0 to 5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] Lithium manganese iron phosphate materials are widely used as positive electrode active materials for batteries due to their good cycle stability, thermal stability, low price and environmental friendliness.

[0057] Lithium manganese iron phosphate materials are usually prepared by high-temperature solid phase method, co-precipitation method, hydrothermal method, etc.; however, in the process of preparing the precursor, wastewater containing a large amount of sulfate ions, chloride ions, and nitrate ions is often generated, which requires further treatment of the wastewater, resulting in complex production processes and high costs.

[0058] In view of the above problems, the embodiment of the present application proposes a method for preparing a lithium iron manganese phosphate composite material. First, an inorganic manganese source, hydrogen peroxide and phosphoric acid are reacted to generate a hydrogen manganese phosphate precursor. In the process of generating the hydrogen manganese phosphate precursor, basically no waste water is generated, and impurity anions and metal ions are not easily introduced; then the hydrogen manganese phosphate precursor is mixed with an M source, a carbon source, etc., and a lithium iron manganese phosphate precursor is formed by spray granulation; then the lithium iron manganese phosphate precursor is calcined at high temperature to generate a lithium iron manganese phosphate composite material.

[0059] Next, the implementation methods of the present application are described in detail.

[0060] Preparation method of lithium manganese iron phosphate composite material

[0061] In a first aspect, an embodiment of the present application provides a method for preparing a lithium manganese iron phosphate composite material.

[0062] The preparation method comprises:

[0063] Step S100, adding phosphoric acid, an inorganic manganese source and a reducing agent into a solvent, reducing manganese ions in the inorganic manganese source to divalent manganese ions under a reducing atmosphere, so that the divalent manganese ions react with phosphoric acid to generate a hydrogen manganese phosphate precursor, wherein the valence state of the manganese ions in the inorganic manganese source is higher than divalent;

[0064] Step S200, mixing an M source, a manganese hydrogen phosphate precursor and a carbon source, grinding and spray granulating to form a manganese iron phosphate lithium precursor, wherein the M source includes an iron source and a lithium source;

[0065] Step S300, calcining a lithium iron manganese phosphate precursor in an inert atmosphere to generate a lithium iron manganese phosphate composite material, wherein the lithium iron manganese phosphate composite material includes lithium iron manganese phosphate particles and a carbon coating layer, and the carbon coating layer is coated on at least a portion of the outer surface of the lithium iron manganese phosphate particles.

[0066] According to the preparation method of the embodiment of the present application, an inorganic manganese source, a reducing agent and phosphoric acid react to form a hydrogen manganese phosphate precursor. This process basically does not require dehydration and drying, is not easy to generate wastewater, and is not easy to introduce impurity anions and metal ions; the hydrogen manganese phosphate precursor, an iron source, a phosphorus source, a lithium source and a carbon source are spray granulated to form a lithium iron manganese phosphate precursor with a relatively small particle size; the lithium iron manganese phosphate precursor is calcined to form a lithium iron manganese phosphate composite material, which includes lithium iron manganese phosphate particles and a carbon coating layer. The lithium iron manganese phosphate particles have a good crystal structure and can improve the compaction density of the lithium iron manganese phosphate particles. The carbon coating layer can improve the electronic conductivity of the lithium iron manganese phosphate composite material and improve the overall electrical conductivity of the lithium iron manganese phosphate composite material.

[0067] [Step S100]

[0068] In some embodiments, the solvent may include deionized water, or a mixture of water and ethanol, etc. Optionally, the solvent is deionized water.

[0069] The manganese ion in the inorganic manganese source has a valence greater than positive divalent, such as positive trivalent, positive tetravalent or positive heptavalent.

[0070] In some embodiments, the inorganic manganese source may include at least one of manganese dioxide and trimanganese tetraoxide; alternatively, the inorganic manganese source may include manganese dioxide.

[0071] In some embodiments, the reducing agent may include at least one of hydrogen peroxide and oxalic acid; alternatively, the reducing agent may include hydrogen peroxide.

[0072] The inorganic manganese source can be a solid substance, that is, a solid inorganic manganese source; the phosphoric acid can be 85% or other concentrations such as 80% phosphoric acid; in order to promote the reaction, the system reaction can be carried out in a grinding state. The solid inorganic manganese source and phosphoric acid can be added to the solvent in advance, and then ground so that the solid inorganic manganese source and the phosphoric acid are fully in contact; then a reducing agent is added to the solvent, and the manganese ions in the inorganic manganese source are reduced to divalent manganese ions under a reducing atmosphere, and the phosphoric acid can promote the reaction between the reducing agent and the inorganic manganese source, so that the manganese ions in the inorganic manganese source are reduced to divalent manganese ions. Since the divalent manganese ions are in full contact with the phosphoric acid, they can react quickly with the phosphoric acid to generate a hydrogen manganese phosphate precursor.

[0073] The reducing agent is in liquid form, such as liquid hydrogen peroxide. When the reducing agent is added to the solvent, the rate of addition of the reducing agent has a certain influence on the reduction process. In order to increase the reduction reaction rate, the manganese ions in the inorganic manganese source are reduced to divalent manganese ions. In some embodiments, the rate of addition of the reducing agent can be 80 mL / min to 120 mL / min, for example, 80 mL / min, 85 mL / min, 90 mL / min, 95 mL / min, 100 mL / min, 105 mL / min, 110 mL / min, 115 mL / min, 120 mL / min or a range consisting of any two of the above values.

[0074] Exemplarily, step S100 may include:

[0075] Step S110, adding a solid inorganic manganese source and solid phosphoric acid into a solvent, stirring and mixing for 5 to 10 minutes, and grinding for 1 to 1.5 hours;

[0076] Step S120, adding a reducing agent to the solvent at a rate of 80 mL / min to 120 mL / min, and under grinding conditions, the reducing agent reacts with the solid inorganic manganese source, the manganese ions in the solid inorganic manganese source are reduced to divalent manganese ions, and the divalent manganese ions react with phosphoric acid to generate a hydrogen manganese phosphate precursor; during the grinding process, the system may undergo a color change, such as from black to white, and gas may be generated. When the color of the system is stable and basically no bubbles are generated, it indicates that the system reaction is basically completed.

[0077] In some embodiments, the ratio of the molar amount of the inorganic manganese source to the molar amount of phosphoric acid is (0.3 to 2.0):1; optionally (0.80 to 1.05):1.

[0078] When the ratio of the molar amount of the inorganic manganese source to the molar amount of phosphoric acid is within the above range, it is conducive to the formation of the manganese hydrogen phosphate precursor. Exemplarily, the ratio of the molar amount of the inorganic manganese source to the molar amount of phosphoric acid is 0.3:1, 0.4:1, 0.5:1:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.05:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1 or a range consisting of any two of the above values.

[0079] In some embodiments, the ratio of the molar amount of the reducing agent to the molar amount of the inorganic manganese source is (1.0 to 1.5):1; optionally (1.05 to 1.5):1.

[0080] When the ratio of the molar amount of the reducing agent to the molar amount of the inorganic manganese source is within the above range, the reducing agent can reduce the manganese ions in the inorganic manganese source to divalent manganese ions, which is beneficial to the subsequent formation of a manganese hydrogen phosphate precursor. For example, the ratio of the molar amount of the reducing agent to the molar amount of the inorganic manganese source can be 1.0:1, 1.05:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1 or a range consisting of any two of the above values.

[0081] Step S100 may be performed under stirring, which is beneficial to sufficient and rapid reaction, and the stirring rate may be 500 r / min to 800 r / min, for example, 500 r / min, 520 r / min, 550 r / min, 560 r / min, 580 r / min, 600 r / min, 620 r / min, 640 r / min, 650 r / min, 680 r / min, 700 r / min, 750 r / min, 800 r / min or a range consisting of any two of the above values.

[0082] [Step S200]

[0083] Since the manganese hydrogen phosphate precursor contains manganese and phosphorus, it can be used as a manganese source and of course also as a phosphorus source.

[0084] The M source may include lithium and iron elements that are essential for lithium iron phosphate. For example, the M source may include a lithium source and an iron source. In order to further improve the compaction density and electrochemical performance of the lithium iron phosphate composite material, the M source may further include a doping source, which can provide at least one of transition metal ions and non-metal ions. Transition metal ions can change the crystal surface energy of lithium iron phosphate particles, thereby allowing the crystal to grow toward a certain surface, which is conducive to grain refinement and improving compaction density and electrochemical performance.

[0085] In some embodiments, the doping element in the doping source may include at least one of titanium, vanadium, chromium, copper, magnesium, aluminum, zinc, cobalt, nickel, tin, niobium, tungsten, zirconium, tantalum, cerium, europium, and fluorine.

[0086] The doping source may include at least one of oxalate, acetate, carbonate, phosphate, oxide, and hydroxide containing the doping element.

[0087] Illustratively, the titanium source may include at least one of titanium oxalate, titanium acetate, titanium carbonate, titanium phosphate, titanium oxide, and titanium hydroxide.

[0088] Illustratively, the vanadium source may include at least one of vanadium oxalate, vanadium acetate, vanadium carbonate, vanadium phosphate, vanadium oxide, and vanadium hydroxide.

[0089] Illustratively, the chromium source may include at least one of chromium oxalate, chromium acetate, chromium carbonate, chromium phosphate, chromium oxide, and chromium hydroxide.

[0090] Illustratively, the copper source may include at least one of copper oxalate, copper acetate, copper carbonate, copper phosphate, copper oxide, and copper hydroxide.

[0091] Illustratively, the magnesium source may include at least one of magnesium oxalate, magnesium acetate, magnesium carbonate, magnesium phosphate, magnesium oxide, and magnesium hydroxide.

[0092] Illustratively, the aluminum source may include at least one of aluminum oxalate, aluminum acetate, aluminum carbonate, aluminum phosphate, aluminum oxide, and aluminum hydroxide.

[0093] Illustratively, the zinc source may include at least one of zinc oxalate, zinc acetate, zinc carbonate, zinc phosphate, zinc oxide, and zinc hydroxide.

[0094] Illustratively, the cobalt source may include at least one of cobalt oxalate, cobalt acetate, cobalt carbonate, cobalt phosphate, cobalt oxide, and cobalt hydroxide.

[0095] Illustratively, the nickel source may include at least one of nickel oxalate, nickel acetate, nickel carbonate, nickel phosphate, nickel oxide, and nickel hydroxide.

[0096] Illustratively, the tin source may include at least one of tin oxalate, tin acetate, tin carbonate, tin phosphate, tin oxide, and tin hydroxide.

[0097] Illustratively, the niobium source may include at least one of niobium oxalate, niobium acetate, niobium carbonate, niobium phosphate, niobium oxide, and niobium hydroxide.

[0098] Illustratively, the tungsten source may include at least one of tungsten oxalate, tungsten acetate, tungsten carbonate, tungsten phosphate, tungsten oxide, and tungsten hydroxide.

[0099] Illustratively, the zirconium source may include at least one of zirconium oxalate, zirconium acetate, zirconium carbonate, zirconium phosphate, zirconium oxide, and zirconium hydroxide.

[0100] Illustratively, the tantalum source may include at least one of tantalum oxalate, tantalum acetate, tantalum carbonate, tantalum phosphate, tantalum oxide, and tantalum hydroxide.

[0101] Illustratively, the cerium source may include at least one of cerium oxalate, cerium acetate, cerium carbonate, cerium phosphate, cerium oxide, and cerium hydroxide.

[0102] Illustratively, the europium source may include at least one of europium oxalate, europium acetate, europium carbonate, europium phosphate, europium oxide, and europium hydroxide.

[0103] For example, the fluorine source may include at least one of fluorooxalic acid fluoride and fluoroacetic acid fluoride. The above lithium source is easily available and can react with other components easily.

[0104] In some embodiments, the lithium source may include at least one of an inorganic lithium source and an organic lithium source. In the case where the lithium source includes phosphorus, it may also serve as a phosphorus source.

[0105] Illustratively, the inorganic lithium source may include at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium phosphate.

[0106] Illustratively, the organic lithium source may include at least one of lithium acetate, lithium oxalate, and lithium citrate.

[0107] In some embodiments, the iron source includes at least one of an inorganic iron source and an organic iron source. The above iron source is easily available and easily reacts with other components. When the iron source includes phosphorus, it can also be used as a phosphorus source.

[0108] Illustratively, the inorganic iron source may include at least one of ferrous carbonate, ferric phosphate, and ferric hydrogen phosphate.

[0109] Illustratively, the organic iron source may include at least one of ferrous oxalate and ferrous acetate.

[0110] In some embodiments, the carbon source may include at least one of a hydroxyl-containing compound and a polyolefin compound. The carbon source can provide carbon coating for the lithium manganese iron phosphate particles and improve the electrochemical properties of the material.

[0111] For example, the hydroxyl-containing compound may include ethylene glycol, glucose, sucrose, polyethylene glycol PEG, polyvinyl alcohol P v A. at least one of citric acid and hydroxypropyl β-cyclodextrin.

[0112] For example, the polyolefin compound may include polyvinyl pyrrolidone P v P, acrylic resin PAA, polyvinylidene fluoride P v At least one of DF, polystyrene and polypropylene.

[0113] In some embodiments, the ratio of the molar amount of the lithium source, the molar amount of the iron source, and the molar amount of the manganese hydrogen phosphate precursor is 1: (0.35 to 0.60): (0.20 to 0.85). . When the molar amount ratio of the lithium source, the iron source, and the manganese hydrogen phosphate precursor is within the above range, the required lithium iron manganese phosphate precursor system can be prepared, and the content of each element in the system is stable. It should be noted that the molar amount of the manganese hydrogen phosphate precursor can be estimated by the relatively smaller molar amount of the molar amount of phosphoric acid and the molar amount of the inorganic manganese source. For example, if the molar amount of phosphoric acid is relatively high, the molar amount of the manganese hydrogen phosphate precursor is estimated by the molar amount of the manganese source; for another example, if the molar amount of phosphoric acid is relatively low, the molar amount of the manganese hydrogen phosphate precursor is estimated by the molar amount of phosphoric acid. Moreover, in the above molar ratio, as the phosphorus content increases, it is easy to cause the primary particles to grow, which helps to increase the compaction density.

[0114] Illustratively, the molar amount of the lithium source, the molar amount of the iron source, and the molar amount of the manganese hydrogen phosphate precursor can have a ratio of 1:0.35:0.85, 1:0.40:0.85, 1:0.45:0.85, 1:0.50:0.85, 1:0.60:0.85, 1:0.40:0.20, 1:0.40:0.50, 1:0.40:0.60, 1:0.40:0.70, 1:0.40:0.85, 1:0.6:0.30, 1:0.60:0.70, 1:0.6:0.85, or a range consisting of any two of the above values.

[0115] The process parameters of the spray granulation in the embodiments of the present application meet the following conditions, which can reduce the particle size of the lithium manganese iron phosphate precursor. In some embodiments, the spray granulation process can set the centrifugal spray dryer inlet temperature to 200°C to 240°C, the outlet temperature to 100°C to 120°C, and the peristaltic feed pump frequency to about 20Hz.

[0116] In step S200, lithium iron manganese phosphate precursors of various particle sizes can be prepared, and then the lithium iron manganese phosphate precursors of various particle sizes can be calcined to obtain lithium iron manganese phosphate composite materials of various particle sizes. By using lithium iron manganese phosphate composite materials of different particle sizes in combination, the compaction density of the lithium iron manganese phosphate composite material can be effectively improved.

[0117] Exemplarily, step S200 may include:

[0118] A lithium source, an iron source, and a manganese hydrogen phosphate precursor are mixed at a first chemical molar ratio, and a carbon source is added to the mixture, and then spray granulated after grinding to form a first manganese iron phosphate lithium precursor;

[0119] A lithium source, an iron source, and a manganese hydrogen phosphate precursor are mixed at a second chemical molar ratio, and a carbon source is added to the mixture, and then spray granulated after grinding to form a second lithium manganese iron phosphate precursor, wherein the volume average particle size of the first lithium manganese iron phosphate precursor is larger than the volume average particle size of the second lithium manganese iron phosphate precursor;

[0120] The first lithium iron manganese phosphate precursor and the second lithium iron manganese phosphate precursor are mixed to form a lithium iron manganese phosphate precursor.

[0121] By preparing a first lithium iron manganese phosphate precursor and a second lithium iron manganese phosphate precursor of two particle sizes, the two powders are mixed and sintered in proportion to grow into primary particles of different sizes, so that the compaction density can be improved by grading the large and small particle sizes. The sintered particles can be further crushed to obtain a lithium iron manganese phosphate composite material of the desired particle size.

[0122] The second chemical molar ratio may be the same as or different from the first chemical molar ratio.

[0123] In some embodiments, the first chemical molar ratio refers to the ratio of the molar amount of the M source to the molar amount of the manganese hydrogen phosphate precursor, and specifically can be the ratio of the molar amount of the lithium source, the molar amount of the iron source, and the molar amount of the manganese hydrogen phosphate precursor, and the ratio is 1: (0.35 to 0.60): (0.20 to 0.85).

[0124] In some embodiments, the second chemical molar ratio refers to the ratio of the molar amount of the M source to the molar amount of the manganese hydrogen phosphate precursor, and specifically can be the ratio of the molar amount of the lithium source, the molar amount of the iron source, and the molar amount of the manganese hydrogen phosphate precursor, and the ratio is 1: (0.35 to 0.60): (0.20 to 0.85).

[0125] In some embodiments, based on the total mass of the lithium iron manganese phosphate precursor, the mass content of the first lithium iron manganese phosphate precursor and the mass content of the second lithium iron manganese phosphate precursor are in a ratio of (10:90) to (30:70), such as 10:90, 11:89, 12:88, 13:87, 14:86, 15:85, 16:84, 17:83, 18:82, 19:81, 20:80, 21:79, 22:78, 23:77, 24:76, 25:75, 26:74, 27:73, 28:72, 29:71, 30:70 or a range consisting of any two of the above values. By combining the first lithium iron manganese phosphate precursor and the second lithium iron manganese phosphate precursor in the above ratio, it is helpful to improve the compaction density of the lithium iron manganese phosphate composite particles and help to exert the capacity.

[0126] In some embodiments, the volume average particle size D of the first lithium manganese iron phosphate precursor is v50 can be 14 μm to 15 μm, for example, 14 μm, 14.1 μm, 14.2 μm, 14.3 μm, 14.4 μm, 14.5 μm, 14.6 μm, 14.7 μm, 14.8 μm, 14.9 μm, 15 μm, or a range consisting of any two of the above values.

[0127] In some embodiments, the volume average particle size D of the second lithium manganese iron phosphate precursor is v 50 may be 13 μm to 14 μm, such as 13 μm, 13.1 μm, 13.2 μm, 13.3 μm, 13.4 μm, 13.5 μm, 13.6 μm, 13.7 μm, 13.8 μm, 13.9 μm, 14 μm, or a range consisting of any two of the above values.

[0128] In the embodiment of the present application, the volume average particle size D of the material v 50 is a well-known meaning in the art, and the volume average particle size D of the material v 50 refers to the particle size corresponding to 50% of the volume distribution, which can be tested by equipment and methods known in the art. A certain amount of composite material is taken as a sample, and the volume average particle size D is tested by Mastersizer2000E laser particle size analyzer according to the test standard GB / T 19077-2016. v 50.

[0129] [Step S300]

[0130] In some embodiments, the inert atmosphere can be an inert gas atmosphere such as nitrogen and argon, which is not easy to react with the lithium iron manganese phosphate precursor and can improve the purity of the final product lithium iron manganese phosphate composite material. In some embodiments, the flow rate of the inert gas can be 3L / min to 8L / min, such as 3L / min, 3.5L / min, 4L / min, 4.5L / min, 5L / min, 5.5L / min, 6L / min, 6.5L / min, 7L / min, 7.5L / min, 8L / min or a range consisting of any two of the above values.

[0131] In some embodiments, the calcination temperature can be 650°C to 750°C, for example 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C or a range consisting of any two of the above values.

[0132] In some embodiments, the heating rate of calcination can be 1°C / min to 5°C / min, for example, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min or a range consisting of any two of the above values.

[0133] Exemplarily, step S300 may include: adding an inert gas at a flow rate of 3 L / min to 8 L / min, increasing the system temperature at a heating rate of 1°C / min to 5°C / min, calcining the lithium iron manganese phosphate precursor at 650°C to 750°C, and cooling to room temperature after keeping warm for 10h to 15h to obtain a lithium iron manganese phosphate composite material.

[0134] Lithium manganese iron phosphate composite material

[0135] In a second aspect, the present application also provides a lithium iron manganese phosphate composite material, which includes lithium iron manganese phosphate particles and a carbon coating layer coated on at least a portion of the surface of the lithium iron manganese phosphate particles. The lithium iron manganese phosphate composite material in the present application can be prepared by the preparation method of any embodiment of the first aspect of the present application, or can be prepared by equipment and methods known in the art.

[0136] In some embodiments, the lithium manganese iron phosphate particles include a molecular formula of Li a Fe x Mn y M z PO4 compound, wherein 1.00≤a≤1.05, 0.1≤x≤0.5, 0.5≤y≤0.9, 0.95≤x+y≤0.98, 0.002≤z≤0.025, and the M element includes at least one element selected from titanium, vanadium, chromium, copper, magnesium, aluminum, zinc, cobalt, nickel, tin, niobium, tungsten, zirconium, tantalum, cerium, europium and fluorine.

[0137] Exemplarily, the lithium manganese iron phosphate particles include LiFe 0.4 Mn 0.6 PO4、LiFe 0.5 Mn 0.5 PO4、LiFe 0.3 Mn 0.7 At least one of PO4.

[0138] In some embodiments, the mass content of the carbon coating layer relative to the total mass of the lithium manganese iron phosphate composite material is 1.3% to 1.6%. The carbon coating layer can provide good protection for the material and improve electronic conductivity, which is beneficial to further slow down the polarization of the material.

[0139] For example, the mass content of the carbon coating layer may be 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt% or a range consisting of any two of the above values.

[0140] In some embodiments, the compaction density of the lithium manganese iron phosphate composite material under a force of 20000N is 2.1 g / cm 3 Up to 2.45g / cm 3 , for example 2.15 g / cm 3 , 2.155g / cm 3 , 2.25g / cm 3 , 2.255g / cm 3 , 2.35g / cm 3 , 2.355g / cm 3 , 2.45g / cm 3 , 2.455g / cm 3 Or a range consisting of any two of the above values.

[0141] In the embodiments of the present application, the compaction density of the material is a well-known meaning in the art and can be tested using commonly used equipment and instruments in the art. The test is performed in accordance with GB / T24533-2009. The bottom area of ​​the material sample added to the UTM7305 electronic pressure testing machine is 1.327 cm 2 The mold is pressurized to 2000kg (equivalent to 20000N), maintained for 30s, then released, maintained for 10s, and then the powder compaction density of the material under a force of 20000N is recorded and calculated.

[0142] In some embodiments, the volume average particle size D of the lithium manganese iron phosphate composite material is v 50 is 0.8 μm to 1.2 μm, for example, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm or a range consisting of any two of the above values.

[0143] In some embodiments, the lithium iron manganese phosphate composite material includes a first particle and a second particle, and the primary particle size of the first particle is larger than the primary particle size of the second particle. By compounding the first particle and the second particle of different particle sizes, the compaction density of the lithium iron manganese phosphate composite material can be effectively improved.

[0144] Optionally, the primary particle size of the first particles is 0.45 μm to 0.6 μm, for example, 0.45 μm, 0.50 μm, 0.55 μm, 0.60 μm or a range consisting of any two of the above values.

[0145] Optionally, the primary particle size of the second particles is 0.10 μm to 0.25 μm, for example, 0.10 μm, 0.15 μm, 0.20 μm, 0.25 μm, or a range consisting of any two of the above values.

[0146] In some embodiments, based on the total mass of the lithium manganese iron phosphate composite material, the ratio of the mass percentage of the first particles to the mass percentage of the second particles is (10:90) to (30:70), for example, 10:90, 11:89, 12:88, 13:87, 14:86, 15:85, 16:84, 17:83, 18:82, 19:81, 20:80, 21:79, 22:78, 23:77, 24:76, 25:75, 26:74, 27:73, 28:72, 29:71, 30:70 or a range consisting of any two of the above values.

[0147] Positive electrode

[0148] In a third aspect, an embodiment of the present application proposes a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes a lithium iron manganese phosphate composite material obtained by the preparation method of any embodiment of the first aspect of the present application, or a lithium iron manganese phosphate composite material as in any embodiment of the second aspect of the present application.

[0149] The lithium iron phosphate particles of the lithium iron manganese phosphate composite material in the positive electrode plate of the embodiment of the present application have a smaller particle size and a relatively high compaction density, and the surface of the lithium iron manganese phosphate particles is coated with a carbon coating layer, which can improve the overall conductivity of the lithium iron manganese phosphate composite material. Therefore, when the positive electrode plate is applied to a battery cell, it can effectively improve the electrochemical performance of the battery cell.

[0150] In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the lithium manganese iron phosphate composite material can be 85wt% to 95wt%. The lithium manganese iron phosphate composite material in this content range can give the positive electrode sheet a higher capacity and better electrochemical performance, thereby improving the energy density and rate performance of the battery cell.

[0151] In some embodiments, the positive electrode active material may further include a positive electrode active material for a battery known in the art in addition to the lithium iron manganese phosphate composite material. As an example, the positive electrode active material may include at least one of the following materials: a layered positive electrode active material (e.g., ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered and rock salt phase layered materials), an olivine-type phosphate active material, a spinel structured positive electrode active material (e.g., spinel lithium manganate, spinel nickel lithium manganate, lithium-rich spinel lithium manganate, and lithium nickel lithium manganate, etc.).

[0152] For example, the general formula of the layered structure positive electrode active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y is selected from one or more of O and F. Optionally, y=0. Specifically, the layered positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) or more.

[0153] Exemplarily, the general formula of the olivine-type phosphate active material is: Li x A y Me a M b P 1-c X c Y z, wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A is selected from one or more of Na, K, and Mg; Me is selected from one or more of Mn, Fe, Co, and Ni; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X is selected from one or more of S, Si, Cl, B, C, and N; and Y is selected from one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0154] For example, the general formula of the positive electrode active material of the spinel structure is: Li x A y Mn a M 2-a Y z , wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y is selected from one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.

[0155] The battery cell will be accompanied by the deintercalation and consumption of active ions such as Li during the charge and discharge process, and the molar content of Li in the battery cell is different when it is discharged to different states. In the list of positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li may change after charge and discharge cycles.

[0156] In the list of positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.

[0157] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application embodiment has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode conductive agent is ≤5%.

[0158] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. The present application embodiment has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and at least one of fluorine-containing acrylic resins. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5%.

[0159] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal material layer formed on at least one surface of the polymer material base. As an example, the metal material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0160] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0161] Battery Cell

[0162] In a fourth aspect, an embodiment of the present application further provides a battery cell.

[0163] A battery cell, also known as a rechargeable battery or storage battery, refers to a battery that can be used continuously by activating the active material by charging after the battery is discharged. Usually, a battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through.

[0164] In some embodiments, the battery cell includes the positive electrode sheet of any embodiment of the second aspect of the embodiment of the present application, or the battery cell includes the positive electrode sheet, and the positive electrode sheet includes the positive electrode sheet of any embodiment of the third aspect of the embodiment of the present application. Therefore, the battery cell of the embodiment of the present application can effectively improve the electrochemical performance of the battery cell.

[0165] [Negative electrode]

[0166] In some embodiments, the battery cell further includes a negative electrode tab.

[0167] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0168] The negative electrode active material may adopt the negative electrode active material for battery cells known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide and tin alloy material.

[0169] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application embodiment has no particular restrictions on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5wt%.

[0170] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The embodiment of the present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5wt%.

[0171] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2wt%.

[0172] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0173] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0174] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the embodiment of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate of the embodiment of the present application further includes a protective layer covering the surface of the negative electrode film layer.

[0175] [Electrolyte]

[0176] In some embodiments, the battery cell further includes an electrolyte.

[0177] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The embodiment of the present application has no particular limitation on the type of electrolyte, which can be selected according to actual needs.

[0178] The electrolyte includes electrolyte salt and solvent. The types of electrolyte salt and solvent are not specifically limited and can be selected according to actual needs.

[0179] When the battery cell of an embodiment of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0180] When the battery cell of an embodiment of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).

[0181] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0182] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.

[0183] [Isolation film]

[0184] The battery cell also includes a separator.

[0185] In some embodiments, the battery cell further includes a separator. The embodiments of the present application have no particular restrictions on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0186] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0187] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.

[0188] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0189] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0190] The present application embodiment has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0191] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0192] The preparation method of the battery cell of the embodiment of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0193] In some embodiments of the embodiments of the present application, the battery cells according to the embodiments of the present application can be assembled into a battery module. The number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0194] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0195] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0196] In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Battery cells, battery modules, and battery packs can all be used as examples of batteries.

[0197] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0198] Electrical devices

[0199] The fifth aspect of the embodiments of the present application provides an electrical device, which includes at least one of the battery cells, battery modules or battery packs of the embodiments of the present application. The battery cells, battery modules or battery packs can be used as power sources for the electrical device, and can also be used as energy storage units for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0200] The electrical device can select a battery cell, a battery module or a battery pack according to its usage requirements.

[0201] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.

[0202] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0203] Example

[0204] The following examples more specifically describe the contents disclosed in the embodiments of the present application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the disclosure of the embodiments of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0205] Example 1-1 Preparation of lithium manganese iron phosphate composite material

[0206] (1) adding deionized water as a solvent to a stirring tank, adding manganese dioxide MnO2 (purity ≥ 93 wt%) and phosphoric acid H3PO4 (purity ≥ 75 wt%) to the deionized water under stirring conditions, and grinding the mixture for 1 h (grinding rate 1000 r / min) using a sand mill to allow the phosphoric acid and manganese dioxide to fully contact;

[0207] Then, hydrogen peroxide (35 wt %) was added to the solvent at a rate of 100 ml / min, and the mixture was ground while reacting until the color of the system in the stirring tank changed from black to white and almost no bubbles were generated, thereby generating a manganese hydrogen phosphate precursor.

[0208] (2) Add ferrous oxalate dihydrate FeC2O4·2H2O (purity ≥ 99 wt%), lithium dihydrogen phosphate LiH2PO4 (purity ≥ 99.5 wt%), lithium carbonate Li2CO3 (purity ≥ 99.5 wt%), glucose (food grade) and polyethylene glycol PEG4000 to the manganese hydrogen phosphate precursor in step (1), stir evenly and grind to a particle size D v 50 is a slurry with a particle size of 0.2 μm to 1 μm (the particle size is calculated based on the refractive index of ferrous oxalate dihydrate);

[0209] The slurry was spray dried using a 10L centrifugal spray dryer to obtain secondary particles D v 50 is a 13μm to 15μm lithium manganese iron phosphate precursor, the inlet air temperature is set to 220℃, the outlet air temperature is controlled at 110℃, and the peristaltic feed pump frequency is set to 20Hz.

[0210] (3) The lithium iron manganese phosphate precursor was sintered in a box furnace, nitrogen was added at a flow rate of 6 L / min, and the temperature was increased at a heating rate of 2°C / min in a nitrogen atmosphere. The calcination temperature was adjusted to 730°C, and the temperature was lowered to room temperature after keeping the temperature for 12 hours to obtain a lithium iron manganese phosphate composite material.

[0211] Comparative Example 1-1 Preparation of lithium manganese iron phosphate composite material

[0212] (1) Add deionized water as solvent to a stirring tank, add manganese oxalate dihydrate MnC2O4·2H2O (purity ≥99.5%, 0.588 mol), ferrous oxalate dihydrate FeC2O4.2H2O (purity ≥99.5%, 0.392 mol), lithium dihydrogen phosphate LiH2PO4 (purity ≥99.5%, 1 mol), lithium carbonate Li2CO3 (purity ≥99.5wt%, 0.01 mol), 6.3 g glucose, and 9.4 g polyethylene glycol PEG4000 to the deionized water under stirring, stir evenly, and then transfer to a ball mill and grind with a planetary ball mill; grind to a particle size of D v 50 is a slurry with a particle size of 0.3 μm to 0.5 μm (the particle size is calculated based on the refractive index of ferrous oxalate dihydrate);

[0213] The slurry was spray dried using a 10L centrifugal spray dryer to obtain D v 50 is a 13μm to 15μm lithium manganese iron phosphate precursor, the inlet air temperature is set to 220℃, the outlet air temperature is controlled at 110℃, and the peristaltic feed pump frequency is set to 20Hz.

[0214] (2) A box-type furnace was used to sinter the lithium iron manganese phosphate precursor, nitrogen was added at a flow rate of 6 L / min, and the temperature was increased at a heating rate of 2°C / min in a nitrogen atmosphere. The calcination temperature was adjusted to 730°C, and the temperature was lowered to room temperature after keeping the temperature for 12 hours to obtain a lithium iron manganese phosphate composite material.

[0215] Example 1-21 to Example 1-23

[0216] A lithium manganese iron phosphate composite material was prepared by a method similar to that of Example 1-1. The difference from Example 1-1 was that the molar amount of at least one of phosphoric acid, manganese dioxide and hydrogen peroxide was adjusted in Examples 1-21 to 1-23.

[0217] Example 1-31 to Example 1-34

[0218] A lithium manganese iron phosphate composite material was prepared by a method similar to that of Example 1-1. The difference from Example 1-1 was that the molar amount of at least one of the lithium source, the iron source, the doping source and the carbon source was adjusted in Examples 1-31 to 1-34.

[0219] Among them, Examples 1-31 to 1-33 do not contain a doping source, and Example 1-34 contains a doping source.

[0220] Example 1-41 to Example 1-45

[0221] A lithium manganese iron phosphate composite material was prepared by a method similar to that of Example 1-1. The difference from Example 1-1 was that the type of at least one of the lithium source, the iron source, the doping source and the carbon source was adjusted in Examples 1-41 to 1-45.

[0222] Example 1-51 to Example 1-55

[0223] (1) adding deionized water as a solvent to a stirring tank, adding manganese dioxide MnO2 (purity ≥ 93 wt%) and phosphoric acid H3PO4 (75 wt%) to the deionized water under stirring conditions, and grinding for 1 h using a sand mill (grinding rate of 1000 r / min) to allow the phosphoric acid and manganese dioxide to fully contact;

[0224] Then, hydrogen peroxide (35 wt %) was added to the solvent at a rate of 100 ml / min, and the mixture was ground while reacting until the color of the system in the stirring tank changed from black to white and almost no bubbles were generated, thereby generating a manganese hydrogen phosphate precursor.

[0225] (2) Add ferrous oxalate dihydrate FeC2O4·2H2O (purity ≥ 99 wt%), lithium dihydrogen phosphate LiH2PO4 (purity ≥ 99.5 wt%), lithium carbonate Li2CO3 (purity ≥ 99.5 wt%), glucose (food grade) and polyethylene glycol PEG4000 to the manganese hydrogen phosphate precursor in step (1), stir evenly and grind to a particle size D v 50 is a slurry with a particle size of 0.2 μm to 1 μm (the particle size is calculated based on the refractive index of ferrous oxalate dihydrate);

[0226] The slurry was spray dried using a 10L centrifugal spray dryer to obtain D v 50 is a first lithium manganese iron phosphate precursor of 13μm to 15μm, the inlet air temperature is set to 220℃, the outlet air temperature is controlled at 110℃, and the peristaltic feed pump frequency is set to 20Hz.

[0227] The slurry was spray dried using a 10L centrifugal spray dryer to obtain D v 50 is a second lithium manganese iron phosphate precursor of 13μm to 15μm, the inlet air temperature is set to 220℃, the outlet air temperature is controlled at 110℃, and the peristaltic feed pump frequency is set to 20Hz.

[0228] The first lithium iron manganese phosphate precursor and the second lithium iron manganese phosphate precursor are mixed to form a lithium iron manganese phosphate precursor.

[0229] (3) The lithium iron manganese phosphate precursor was sintered in a box furnace, nitrogen was added at a flow rate of 6 L / min, and the temperature was increased at a heating rate of 2°C / min in a nitrogen atmosphere. The calcination temperature was adjusted to 730°C, and the temperature was lowered to room temperature after keeping the temperature for 12 hours to obtain a lithium iron manganese phosphate composite material.

[0230] Preparation of Lithium Ion Batteries in Examples and Comparative Examples

[0231] 1. Preparation of positive electrode sheet

[0232] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0233] The positive electrode active material lithium manganese iron phosphate composite material, the conductive agent carbon black, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone NMP at a weight ratio of 80:10:10 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0234] 2. Preparation of negative electrode sheet

[0235] Lithium foil is used as the negative electrode.

[0236] 3. Isolation film

[0237] A porous polyethylene (PE) film is used as the isolation membrane.

[0238] 4. Preparation of electrolyte

[0239] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then lithium salt lithium hexafluorophosphate and the electrolyte solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0240] 5. Preparation of battery cells

[0241] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0242] The relevant parameters of the embodiments and comparative examples are shown in Tables 1 to 4.

[0243] Performance Testing

[0244] 1. Discharge capacity test of lithium-ion battery

[0245] At 25°C, charge to 4.3V at a constant current of 0.1C, then charge at a constant voltage of 4.3V until the current drops to 0.02C, and then discharge to 2V at a constant current of 0.1C to obtain the first cycle discharge specific capacity, the unit of which is mAh / g.

[0246] At 25°C, charge to 4.3V at a constant current of 0.33C, then charge at a constant voltage of 4.3V until the current drops to 0.02C, and then discharge to 2V at a constant current of 0.33C to obtain the first cycle discharge specific capacity, the unit of which is mAh / g.

[0247] At 25°C, charge to 4.3V at a constant current of 1C, then charge at a constant voltage of 4.3V until the current drops to 0.02C, and then discharge to 2V at a constant current of 1C to obtain the first cycle discharge specific capacity, the unit of which is mAh / g.

[0248] Test Results

[0249] The test results are shown in Tables 1 to 4.

[0250] Table 1

[0251]

[0252]

[0253] Table 2

[0254]

[0255] In Table 1 and Table 2,

[0256] The molar ratio of the inorganic manganese source to the phosphoric acid represents the ratio of the molar amount of the inorganic manganese source to the molar amount of the phosphoric acid. The molar amount of the lithium source includes the total molar amount of LiH2PO4 and Li2CO3. The molar ratio of the iron source to the lithium source is the ratio of the molar amount of FeC2O4·2H2O to (the total molar amount of LiH2PO4 and Li2CO3).

[0257] The molar amount of the manganese hydrogen phosphate precursor can be the relatively smaller molar amount of phosphoric acid and the inorganic manganese source. For example, if the molar amount of phosphoric acid is relatively high, the molar amount of the manganese hydrogen phosphate precursor is estimated by the molar amount of the inorganic manganese source; for another example, if the molar amount of phosphoric acid is relatively low, the molar amount of the manganese hydrogen phosphate precursor is estimated by the molar amount of phosphoric acid.

[0258] Table 3

[0259]

[0260] In Table 3, Examples 1-N represent the types of lithium iron manganese phosphate composite materials, and Example 2-N represents lithium ion batteries prepared using the lithium iron manganese phosphate composite materials of Examples 1-N as positive electrode active materials; wherein N represents a number, for example, 1, 21, 22, 23, 31, etc.

[0261] Comparative Example 1-1 represents the type of lithium iron manganese phosphate composite material, and Comparative Example 2-1 represents a lithium ion battery prepared by using the lithium iron manganese phosphate composite material of Comparative Example 1-1 as a positive electrode active material.

[0262] The compacted density of the lithium iron manganese phosphate composite material prepared in Comparative Example 1-1 is relatively low; the present application generates a hydrogen manganese phosphate precursor by pre-reacting an inorganic manganese source, hydrogen peroxide and phosphoric acid, and basically no waste water is generated in the process of generating the hydrogen manganese phosphate precursor, and it is not easy to introduce impurity anions and metal ions; the hydrogen manganese phosphate precursor is then mixed with an M source, a carbon source, etc., and a lithium iron manganese phosphate precursor is formed by spray granulation; the lithium iron manganese phosphate precursor is then calcined at a high temperature to generate a lithium iron manganese phosphate composite material, which has a relatively high compacted density and is beneficial to the improvement of the battery discharge specific capacity.

[0263] Table 4

[0264]

[0265] Table 5

[0266]

[0267] In Table 4, in Examples 1-51 to 1-55, the molar amount of the lithium source in the first lithium iron manganese phosphate precursor is 1.02 mol, and the molar amount of phosphoric acid is 1 mol. In Examples 1-51 to 1-55, the molar amount of the lithium source in the second lithium iron manganese phosphate precursor is 1.02 mol, and the molar amount of phosphoric acid is 1 mol.

[0268] The parameters not shown in Table 4 are similar to those in Example 1-1 and are not described again here.

[0269] In Table 5, the first particle is obtained by sintering the first lithium iron manganese phosphate precursor, and the second particle is obtained by sintering the second lithium iron manganese phosphate precursor.

[0270] It can be seen from Tables 4 and 5 that when preparing the lithium iron manganese phosphate precursor, preparing the lithium iron manganese phosphate precursor with different particle sizes is more conducive to improving the compaction density of the final lithium iron manganese phosphate composite material.

[0271] Combination Figure 7 It can be seen that 1.00 μm is divided into 10 small grids, each grid is 0.1 μm, and the lithium manganese iron phosphate composite material in Example 1-51 includes primary particles of different particle sizes, the smallest primary particle is about 100 nm, and the largest primary particle is about 500 nm. There are some gaps between the particles that will affect the compaction density. The present application improves the compaction density by filling small particles between large particles.

[0272] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A method for preparing a lithium manganese iron phosphate composite material, characterized in that: include: Adding phosphoric acid, an inorganic manganese source and a reducing agent into a solvent, reducing manganese ions in the inorganic manganese source to divalent manganese ions under a reducing atmosphere, so that the divalent manganese ions react with the phosphoric acid to generate a hydrogen manganese phosphate precursor, wherein the valence state of the manganese ions in the inorganic manganese source is higher than divalent; Mixing an M source, the manganese hydrogen phosphate precursor and a carbon source, grinding and spray granulating to form a lithium manganese iron phosphate precursor, wherein the M source includes an iron source and a lithium source; The lithium iron manganese phosphate precursor is calcined in an inert atmosphere to generate a lithium iron manganese phosphate composite material, wherein the lithium iron manganese phosphate composite material includes lithium iron manganese phosphate particles and a carbon coating layer, and the carbon coating layer is coated on at least a portion of the outer surface of the lithium iron manganese phosphate particles.

2. The preparation method according to claim 1, characterized in that: The inorganic manganese source comprises at least one of manganese dioxide and manganese tetraoxide; and / or The reducing agent includes at least one of hydrogen peroxide and oxalic acid.

3. The preparation method according to claim 1 or 2, characterized in that: The ratio of the molar amount of the inorganic manganese source to the molar amount of the phosphoric acid is (0.3 to 2.0):1; optionally (0.80 to 1.05):1; and / or The ratio of the molar amount of the reducing agent to the molar amount of the inorganic manganese source is (1.0 to 1.5):1; optionally, it is (1.05 to 1.5):

1.

4. The preparation method according to any one of claims 1 to 3, characterized in that The lithium source includes at least one of an inorganic lithium source and an organic lithium source; optionally, the inorganic lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate and lithium phosphate; optionally, the organic lithium source includes at least one of lithium acetate, lithium oxalate and lithium citrate; and / or The iron source includes at least one of an inorganic iron source and an organic iron source; optionally, the inorganic iron source includes at least one of ferrous carbonate, ferric phosphate, and ferrous hydrogen phosphate; the organic iron source includes at least one of ferrous oxalate and ferrous acetate; and / or The carbon source includes at least one of a hydroxyl-containing compound and a polyolefin compound; optionally, the hydroxyl-containing compound includes at least one of ethylene glycol, glucose, sucrose, polyethylene glycol, polyvinyl alcohol, citric acid and hydroxypropyl β-cyclodextrin; the polyolefin compound includes at least one of polyvinyl pyrrolidone, acrylic resin, polyvinylidene fluoride, polystyrene and polypropylene.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The ratio of the molar amount of the lithium source, the molar amount of the iron source and the molar amount of the manganese hydrogen phosphate precursor is 1: (0.35 to 0.60): (0.20 to 0.85).

6. The preparation method according to any one of claims 1 to 5, characterized in that The M source also includes a doping source, and the doping elements in the doping source include at least one element selected from titanium, vanadium, chromium, copper, magnesium, aluminum, zinc, cobalt, nickel, tin, niobium, tungsten, zirconium, tantalum, cerium, europium and fluorine.

7. The preparation method according to any one of claims 1 to 6, characterized in that The step of mixing the M source, the manganese hydrogen phosphate precursor and the carbon source, grinding and spray granulating to form the lithium manganese iron phosphate precursor comprises: Mixing the M source and the manganese hydrogen phosphate precursor, adding a carbon source, grinding, and spray granulating to form a first lithium manganese iron phosphate precursor; Mixing the M source and the manganese hydrogen phosphate precursor, adding a carbon source, and grinding and spray granulating to form a second lithium manganese iron phosphate precursor, wherein the volume average particle size of the first lithium manganese iron phosphate precursor is larger than the volume average particle size of the second lithium manganese iron phosphate precursor; The first lithium iron manganese phosphate precursor and the second lithium iron manganese phosphate precursor are mixed to form a lithium iron manganese phosphate precursor.

8. The preparation method according to claim 7, characterized in that: The volume average particle size D of the first lithium manganese iron phosphate precursor v 50 is 14 μm to 15 μm; and / or The volume average particle size D of the second lithium manganese iron phosphate precursor v 50 is 13 μm to 14 μm; and / or Based on the total mass of the lithium iron manganese phosphate precursor, a ratio of the mass content of the first lithium iron manganese phosphate precursor to the mass content of the second lithium iron manganese phosphate precursor is (10:90) to (30:70).

9. A lithium manganese iron phosphate composite material, characterized in that: The invention comprises lithium iron manganese phosphate particles and a carbon coating layer coated on at least a part of the surface of the lithium iron manganese phosphate particles, wherein the lithium iron manganese phosphate particles include a molecular formula of Li a Fe x Mn y M z PO4 compound, wherein 1.00≤a≤1.05, 0.1≤x≤0.5, 0.5≤y≤0.9, 0.95≤x+y≤0.98, 0.002≤z≤0.025, and the M element includes at least one element selected from titanium, vanadium, chromium, copper, magnesium, aluminum, zinc, cobalt, nickel, tin, niobium, tungsten, zirconium, tantalum, cerium, europium and fluorine.

10. The lithium iron manganese phosphate composite material according to claim 9, characterized in that: The lithium manganese iron phosphate composite material meets at least one of the following conditions: (1) The compaction density of the lithium manganese iron phosphate composite material under a force of 20000N is 2.10g / cm 3 Up to 2.45g / cm 3 ; (2) Volume average particle size D of lithium manganese iron phosphate composite material v 50: 0.8 μm to 1.2 μm; (3) The lithium manganese iron phosphate composite material comprises a first particle and a second particle, wherein the primary particle size of the first particle is larger than the primary particle size of the second particle; optionally, the primary particle size of the first particle is 0.45 μm to 0.6 μm; and / or the primary particle size of the second particle is 0.10 μm to 0.25 μm; Optionally, based on the total mass of the lithium manganese iron phosphate composite material, a ratio of the mass percentage of the first particles to the mass percentage of the second particles is (10:90) to (30:70).

11. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium iron manganese phosphate composite material prepared by the preparation method according to any one of claims 1 to 8, or a lithium iron manganese phosphate composite material according to claim 9 or 10.

12. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11.

13. An electrical device, characterized in that: Comprising the battery of claim 12, the battery being used to provide electrical energy.

Citation Information

Cited By

  • Carbon-based energy storage electrode material, preparation method thereof, supercapacitor and application

    CN121553937A